2015
DOI: 10.1016/j.rmcr.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Timolol-induced interstitial lung disease

Abstract: Timolol maleate is a non-selective beta-adrenergic receptor blocking agent with demonstrated efficacy in the treatment of open-angle glaucoma. A 76 year old female who presented with productive cough, progressive dyspnea and hypoxia after starting timolol maleate opthalamic drops following glaucoma surgery. The patient was diagnosed with interstitial lung disease secondary to timolol treatment and after cessation of the offending agent along with corticosteroid treatment, symptoms improved drastically. Elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“… 18 19 Timolol-induced interstitial lung disease was reported: a 76-year-old woman presented with productive cough and progressive dyspnoea and hypoxia after starting timolol eye drop use following glaucoma surgery. 20 It was also reported that an elderly patient was hospitalised with three side effects of timolol. His condition required intensive care unit admission with mechanical ventilation and temporary transvenous pacing.…”
Section: Discussionmentioning
confidence: 98%
“… 18 19 Timolol-induced interstitial lung disease was reported: a 76-year-old woman presented with productive cough and progressive dyspnoea and hypoxia after starting timolol eye drop use following glaucoma surgery. 20 It was also reported that an elderly patient was hospitalised with three side effects of timolol. His condition required intensive care unit admission with mechanical ventilation and temporary transvenous pacing.…”
Section: Discussionmentioning
confidence: 98%
“…Interstitial lung disease clusters many subacute and chronic respiratory conditions characterized by compromising the pulmonary parenchyma, mainly affecting the interstitium and alveolar spaces [ 14 , 15 ]. The lung interstitium in ILDs is involved during inflammation and fibrosis processes.…”
Section: Introductionmentioning
confidence: 99%